Rocky forms in the Yamna Sandstone (Skyba Nappe, Outer Carpathians, Ukraine) - Waśkowska, Anna; Hnylko, Svitlana; Bakayeva, Sofia; Golonka, Jan; Słomka, Tadeusz; Heneralova, Larysa (Geotourism/Geoturystyka, 2020)
Interesting objects – the rocky forms and waterfall thresholds, built of Yamna Sandstone occur in the vicinity of Skole town. Beside the esthetic positive aspects related the morphological variety of the rocky forms and occurrence of the diversified weathering structures, the objects have a substantial cognitive value encompassing the lithology and sedimentological processes of the thick-bedded turbidites. The sandstone rocky forms usually occur in the groups distributed on slopes and forming so-called rocky towns. Their number and distribution allow observation of the changing structural and textural features both lateral and vertical within the 100-m thick composed profiles. The excellent degree of rocks outcropping, variety of structural and textural features and spectrum of possible observations indicates the high geotouristic potential of the investigated objects.